Impact of Retroflexion Vs. Second Forward View Examination of the Right Colon on Adenoma Detection: A Comparison Study. (March 2015) - Kushnir, Vladimir M; Oh, Young S; Hollander, Thomas; Chen, Chien‐Huan; Sayuk, Gregory S; Davidson, Nicholas; Mullady, Daniel; Murad, Faris M; Sharabash, Noura M; Ruettgers, Eric; Dassopoulos, Themistocles; Easler, Jeffrey J; et al.
Abstract : OBJECTIVES: Although screening colonoscopy is effective in preventing distal colon cancers, effectiveness in preventing right‐sided colon cancers is less clear. Previous studies have reported that retroflexion in the right colon improves adenoma detection. We aimed to determine whether a second withdrawal from the right colon in retroflexion vs. forward view alone leads to the detection of additional adenomas. METHODS: Patients undergoing screening or surveillance colonoscopy were invited to participate in a parallel, randomized, controlled trial at two centers. After cecal intubation, the colonoscope was withdrawn to the hepatic flexure, all visualized polyps removed, and endoscopist confidence recorded on a 5‐point Likert scale. Patients were randomized to a second exam of the proximal colon in forward (FV) or retroflexion view (RV), and adenoma detection rates (ADRs) compared. Logistic regression analysis was used to evaluate predictors of identifying adenomas on the second withdrawal from the proximal colon. RESULTS: A total of 850 patients (mean age 59.1±8.3 years, 59% female) were randomly assigned to FV ( N =400) or RV ( N =450). Retroflexion was successful in 93.5%. The ADR (46% FV and 47% RV) and numbers of adenomas per patient (0.9±1.4 FV and 1.1±2.1 RV) were similar ( P =0.75 for both). At least one additional adenoma was detected on second withdrawal in similar proportions (10.5% FV and 7.5% RV, P =0.13). Predictors of identifying adenomas on the second withdrawal included older age (odds ratio (OR)=1.04, 95% confidence interval (CI)=1.01–1.08), adenomas seen on initial withdrawal (OR=2.8, 95% CI=1.7–4.7), and low endoscopist confidence in quality of first examination of the right colon (OR=4.8, 95% CI=1.9–12.1). There were no adverse events. CONCLUSIONS: Retroflexion in the right colon can be safely achieved in the majority of patients undergoing colonoscopy for colorectal cancer screening. Reexamination of the right colon in either retroflexed or forward view yielded similar, incremental ADRs. A second exam of the right colon should be strongly considered in patients who have adenomas discovered in the right colon, particularly when endoscopist confidence in the quality of initial examination is low.